Identification of Factors and Models of Knowledge Management Maturity: A Systematic Literature Review - Abilowo, Krisanto; Sensuse, Dana Indra (Jambura Journal of Informatics, 2026)
Studies related to the knowledge management maturity (KMM) model in libraries have been successfully identified. However, the model is at risk of bias because, in these studies, the KMM assessment within the organization is based on the total score across all criteria/components/factors. This poses a risk of bias if one of the criteria required at the initial maturity level is not met. Therefore, this study aims to identify KMM factors and models from various sectors to support research on developing a KMM model in the library sector. In identifying KMM factors and models, the researchers will conduct a Systematic Literature Review (SLR). The method used in this SLR is the Kitchenham method. Of the 103 KMM factors, the most widely used in previous studies were in the process category, including organizational culture. Based on the factors that make up the KMM model, it can be seen that, among the 17 KMMs, those used in previous studies had the greatest advantages in the process category, such as the army KM3. In addition, based on the objectives of the KMM model, one model that assesses the maturity level of Knowledge Management (KM) implementation and serves as a guideline for KM implementation is the General KM Maturity Model (GKMMM). Based on the issues and results of the SLR conducted, the researchers plan to develop a knowledge management maturity model for the library sector in the next study.